Multi-Paging Technology for Emergency Rooms (المجلة الدولية للبحوث العلمية, 2024)
This report presents the design, implementation and testing of a multi-paging device that should be installed in ERs “Emergency Rooms” to page doctors by more than one method. The designed multi-paging device was successful in paging the specific contact as will be shown at the end of this paper.